(untitled) (ENTHYMEMA, 2013)
This is the first translation into Italian of Paul Ricœur’s preface to Lucio Saffaro’s Théorie de la poursuite, L’Alphée, Paris 1985. The present text is published with permission from Fonds Ricœur, and is also enriched with drawings made by Lucio Saffaro, published with authorization from Fondazione Lucio Saffaro. The text is followed by a short outline of Saffaro’s work by Gisella Vismara.